Anaerobic Ammonium Oxidation (Anammox) Pada Penyisihan Nitrogen Air Limbah Domestik - I Made Wahyu Wijaya; Putu Eka Dharma Putra (Jurnal Ecocentrism, 2021)
Domestic wastewater effluent is the main contributor to diverse water pollution problems. The contaminants contained in the wastewater lead the low quality of water. The presence of ammonium and nitrate along with phosphorus are potentially cause eutrophication and endanger aquatic life. It increases the growth rate of algae and pressing down the dissolved oxygen which is highly corresponding to the death of aquatic animal due to anaerobic condition. Excess nutrients, mostly N and P is main cause of eutrophication which is result in oxygen depletion, biodiversity reduction, fish kills, odor and increased toxicityAn advance biological nitrogen removal process called anammox is a sustainable and cost effective alternative to the basic method of nitrogen removal, such as nitrification and denitrification. Many research have been conducted through anammox and resulted promisingly way to remove nitrogen. In this process, ammonium will be oxidized with nitrite as electron acceptor to produce nitrogen gas and low nitrate in anoxic condition. Anammox requires less oxygen demand, no needs external carbon source and low operational cost. Based on its advantages, anammox is possible to apply in domestic wastewater treatment with many further studies.